EVIDENCES OF A RITUAL BURIAL IN A RESIDENTIAL SECTOR OF THE HIGH PART OF CARAL, SUPE VALLEY - Espinoza, Arturo Noel (2002)
The preliminary results of the research done in one of the precinct ofResidential Sector A, located in the middle high ofthe archaeological site ofCaral (3000-2000 B.C.)-Supe Valley are presented. The data describe the successive ritual burial ofthat precinct, correlated with the definition oj the different constructive phases ofthe contiguous precincts.